Outcome of Overuse Smartphones on Psychosocial Status in Early Aged Children (3-6years) - Sahib, Ahmed Makki; A. Hasan, Abdul Mahdi (Journal of Neonatal Surgery, 2025)
Background: The smartphone is one of the most widely used products among adults and kids alike. Nowadays, not a single child is unaware of smartphones. Compared to adults, they can occasionally use all of its applications more skillfully. Despite the fact that children shouldn't use smartphones for extended periods of time as this could harm their health. furthermore, Physical, psychosocial, and cognitive development are crucial in early childhood and play a significant during the preschool years' role in shaping children's psychosocial, behavioral, and academic outcomes. The effects of smartphones on preschoolers' psychological is a topic of growing concern in today's society. Investigators have been concerned about preschoolers' excessive use of electronics, including smartphones and gadgets. High frequency of media usage in early childhood is probably going to negatively impact to psychosocial development, including emotional and behavioral issues, physical activity, sleep, and obesity, according to a literature analysis by (Paulus et al., 2021). Objectives: This study aimed to assess of overuse of smartphones on psychosocial status in early aged (3-6 years) children and examine relationship between overuse of smartphones on psychosocial status in early aged children. Methodology: A descriptive correlation quantitative approach is used. starting from November 9th 2023 to January 12th 2025, with data collecting included selecting (132) child selected for those who visits and benefited of Maternal and Child Health Unit services (MCHs) in Primary Health Care Centers (PHHCs) of Al-Najaf City, Iraq. Participants were selected based on specific criteria, including the children age group was between (3 to 6) years who attained primary health center for both North and South sectors during the time of data collection for the current study, being able to read and write (parents). Participants who had excessive use of electronic devices more than half an hour. Children who use of touchscreen devices such as smartphones or tablet computers or mobile or T.V. Problematic Technology Use Scale for excessive use of smartphones for young children (PTUS-YC) is a validated tool to measure an excessive use of electronic devices levels. Items of the instrument were grammatically correct and easy for the reader to understand, every child parent should answer these questions with one of the choices, A 5-point Likert scale was constructed for measuring according the following: (Completely Disagree=1, Somewhat Disagree=2, Undecided=3, Somewhat Agree=4, completely Agree=5), (Konca, 2022), The scale does not require special permission for use, as it is a globally recognized and publicly accessible measurement tool. And Psychosocial status of the child (PSAS 3–6) includes these 31 items in PSAS 3–6 scale for the child were used to measure overuse of smartphones on psychosocial status in early aged children and psycho-social status. The researcher applies five Likert type options: 0 for "never," 1 for "rarely," 2 for "sometimes," 3 for "often," and 4 for "always." A minimum score of 0 and a maximum score of 124 points can be obtained from the questionnaire, depending on the score assigned to each item. Results: The result of assessment of excessive use of electronic devices that showed mostly of preschool children square of sample (30.3%) have a high excessive use of smartphone devices. Overall Psychosocial status of the child show that less than three quadrants of preschool more than (71.2%) have a moderate psychosocial distress. Conclusion: It was noteworthy that an important number of preschool children reported excessive use of electronic devices. Psychosocial Impact: The analysis indicated an obvious correlation between excessive usage of electronic devices and negative psychosocial impacts on preschool children. Some children reported problems such as expressively emotional, aggressive speech and social withdrawal behaviors. Near to half of percent of children that were analyzed were reported to have moderate problematic behavior. Recommendations: Development of awareness programs and policies aimed at reducing the negative health effects of excessive electronic device use among children. Parents and guardians need to set specific rules for screen engagement for their children.